Soft Lithography and Minimally Human Invasive Technique for Rapid Screening of Oral Biofilm Formation on New Microfabricated Dental Material Surfaces - Marta Alvarez-Escobar; Sidónio C. Freitas; Derek Hansford; Fernando J. Monteiro; Alejandro Pelaez-Vargas (Hindawi Limited, 2018)
Introduction. Microfabrication offers opportunities to study surface concepts focused to reduce bacterial adhesion on implants using human minimally invasive rapid screening (hMIRS). Wide information is available about cell/biomaterial interactions using eukaryotic and prokaryotic cells on surfaces of dental materials with different topographies, but studies using human being are still limited. Objective. To evaluate a synergy of microfabrication and hMIRS to study the bacterial adhesion on micropatterned surfaces for dental materials. Materials and Methods. Micropatterned and flat surfaces on biomedical PDMS disks were produced by soft lithography. The hMIRS approach was used to evaluate the total oral bacterial adhesion on PDMS surfaces placed in the oral cavity of five volunteers (the study was approved by the University Ethical Committee). After 24 h, the disks were analyzed using MTT assay and light microscopy. Results. In the present pilot study, microwell structures were microfabricated on the PDMS surface via soft lithography with a spacing of 5 µm. Overall, bacterial adhesion did not significantly differ between the flat and micropatterned surfaces. However, individual analysis of two subjects showed greater bacterial adhesion on the micropatterned surfaces than on the flat surfaces. Significance. Microfabrication and hMIRS might be implemented to study the cell/biomaterial interactions for dental materials.